Electromigration and morphological changes in Ag nanostructures. (31st January 2018) - Chatterjee, A; Bai, T; Edler, F; Tegenkamp, C; Weide-Zaage, K; Pfnür, H
Abstract: Electromigration (EM) as a structuring tool was investigated in Ag nanowires (width 300 nm, thickness 25 nm) and partly in notched and bow-tie Ag structures on a Si(1 0 0) substrate in ultra-high vacuum using a four-tip scanning tunneling microscope in combination with a scanning electron microscope. From simulations of Ag nanowires we got estimates of temperature profiles, current density profiles, EM and thermal migration (TM) mass flux distributions within the nanowire induced by critical current densities of 10 8 A cm −2 . At room temperature, the electron wind force at these current densities by far dominates over thermal diffusion, and is responsible for formation of voids at the cathode and hillocks at the anode side. For current densities that exceed the critical current densities necessary for EM, a new type of wire-like structure formation was found both at room temperature and at 100 K for notched and bow-tie structures. This suggests that the simultaneous action of EM and TM is structure forming, but with a very small influence of TM at low temperature.